Effect on Renal Function of Restoration of Euthyroidism in Hyperthyroid Cats with Iatrogenic Hypothyroidism. (28th April 2014) - Williams, T.L.; Elliott, J.; Syme, H.M.
<x xml:space="preserve">Abstract</x> Background Iatrogenic hypothyroidism is associated with an increased incidence of azotemia after treatment of hyperthyroidism, and decreased survival time in azotemic hyperthyroid cats. Hypothesis Restoration of euthyroidism will decrease plasma creatinine concentrations. Animals Nineteen client‐owned, methimazole‐ or carbimazole‐treated, hyperthyroid cats with documented iatrogenic hypothyroidism (based on subnormal plasma total thyroxine concentrations [TT4] and increased plasma thyroid‐stimulating hormone concentrations). Methods Prospective interventional study. Doses of antithyroid medication were reduced until euthyroidism was restored (TT4 10–40 nmol/L). Plasma creatinine concentration and selected other clinicopathologic variables were evaluated before and after restoration of euthyroidism and compared by nonparametric statistics. Data are presented as median [25th, 75th percentile]. Results Restoration of euthyroidism was associated with a significant decrease in plasma creatinine concentrations (2.61 [1.90, 3.26] mg/dL versus 2.07 [1.42, 2.82] mg/dL; P < .001) and body weight (4.03 [3.59, 4.53] kg versus 3.89 [3.34, 4.18] kg; P = .019), and a significant increase in packed cell volume (30 [28, 39]% versus 34 [29, 39]%; P = .038), heart rate (174 [163, 201] bpm versus 190 [164, 202] bpm; P = .009), and plasma alkaline phosphatase activity (26.6 [17.0, 33.0] IU/L versus 38.0 [23.5, 46.5] IU/L; P < .001). Conclusions and Clinical Importance Restoration of euthyroidism in medically treated hyperthyroid cats with iatrogenic hypothyroidism causes a reduction in plasma creatinine concentrations, and thus might improve renal function; however, this could be influenced by concurrent changes in body weight.